MANAJEMEN GURU RAUDLATUL ATHFAL DALAM TOTAL QUALITY MANAGEMENT - Fu’ad Arif Noor (Nizham Jurnal Studi Keislaman, 2014)
This study was to determine the level of academic qualifications, competence, and especially teacher certification Raudlatul Athfal teacher management component contained in the Total Quality Management ( TQM ).Quality education will only be realized if the available qualified teachers. To realize the required qualified teachers effective teacher management ranging from recruitment, placement, induction, welfare and professional development of teachers. The teacher is a person who works to teach, so teachers Raudlatul Athfal ( RA ) is a teacher who teaches in the Early Childhood education units ( ECD ) in the levels of formal Raudlatul RA or kindergarten who have the ability as an educator and responsible learners .In TQM (Total Quality Management), the authors sought to find alternative thinking menukilkan teacher management Raudlatul Athfal ( RA ) is an effective starting from recruitment and placement system, indusksi and welfare benefits, as well as the professional development of teachers. Effective teacher management began perkrutan, placement, induction of new teachers, good welfare, and sustainable professional development.